CURRENT STATUS AND CHALLENGES IN THE MANAGEMENT OF POST-ABLATIVE HYPOTHYROIDISM DUE TO GRAVES’ DISEASE AMONG THAI PATIENTS - Mathiphanit, Saravut; Chatchomchuan, Waralee; Butadej, Siriwan; Himathongkam, Thep; Thewjitcharoen, Yotsapon (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Up to 40% of patients on levothyroxine (LT4) replacement have out-of-range TSH. This study aimed to evaluate TSH and daily LT4 dosage according to body mass index (BMI) in Thai patients with post-ablative hypothyroidism. METHODOLOGY We reviewed the medical records of Thai patients treated with radioactive iodine (RAI) for Graves’ disease from 2016 to 2020 at Theptarin Hospital. Patients who received LT4 for at least 6 months were included. Serum TSH, FT4 and self-reported compliance were retrieved at the last visit. Daily LT4 dose was calculated based on actual body weight (ABW) compared with estimated lean body mass (LBM) by Hume formula. RESULTS A total of 271 patients (female 81.2%, mean age 36.7 ± 7.6 years, LT4 treatment duration 27.1±14.6 months, LT4 1.4±0.5 μg/kg ABW/day, LT4 2.0 ± 0.7 μg/kg LBM/day) were analyzed. Only 55.5% of patients achieved within-range TSH on last follow-up. TSH values were above reference range (>4.2 mIU/L) in 15.1% and below (<0.3 mIU/L) in 29.9%. Only 3.3% of all patients frequently missed dose of LT4 more than 15%. Within-range TSH was seen in 46.2% of obese patients (BMI ≥30 kg/m2). There were no differences between daily LT4 doses based on ABW and LBM between within-range and out-of-range TSH groups. Obese patients required a lower daily LT4 dose relative to ABW and LBM to attain euthyroidism (ABW 1.1 ± 0.4 μg/ kg/day and LBM 1.8 ± 0.6 μg/kg/day). CONCLUSION Almost 50% of patients with hypothyroidism had out-of- range TSH values. In obese patients, both ABW and LBM could be used to guide appropriate LT4 replacement dose.